2020
DOI: 10.1371/journal.pone.0238251
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome atlas for differentiating tumor stage and post-surgical prognosis of hepatocellular carcinoma and cholangiocarcinoma

Abstract: Although mass spectrometry-based plasma proteomics enables sensitive and large-scale discovery and validation of biomarkers for various diseases, its integrative application to hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) is not well investigated. Therefore, we analyzed albumin-and immunoglobulin G-depleted plasma samples from 148 and 60 patients with HCC and CCA, respectively, using liquid chromatography-tandem mass spectrometry. The algorithm used to measure the content of each protein was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Interestingly, the authors reported that levels of plasma serine protease inhibitor inversely correlated with tumour development (stage I to IV). In addition, levels of afamain - a human plasma vitamin E-binding glycoprotein, and previously described ovarian cancer tumour marker ( 157 ), were associated with poor prognosis in CCA ( 156 ). Despite their potential, these similarly require further validation in larger and randomized cohorts.…”
Section: Diagnostic and Prognostic Biomarkers In Ccamentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the authors reported that levels of plasma serine protease inhibitor inversely correlated with tumour development (stage I to IV). In addition, levels of afamain - a human plasma vitamin E-binding glycoprotein, and previously described ovarian cancer tumour marker ( 157 ), were associated with poor prognosis in CCA ( 156 ). Despite their potential, these similarly require further validation in larger and randomized cohorts.…”
Section: Diagnostic and Prognostic Biomarkers In Ccamentioning
confidence: 94%
“…Other serum proteins have been reported as stage specific and prognostic in CCA. A recent study analysed the serum proteome of 148 HCC and 60 CCA patients by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and found 25 differently expressed proteins in CCA patients, with AUC ranging from 0.701 to 0.823 ( 156 ). Interestingly, the authors reported that levels of plasma serine protease inhibitor inversely correlated with tumour development (stage I to IV).…”
Section: Diagnostic and Prognostic Biomarkers In Ccamentioning
confidence: 99%
“…Liquid biopsies in combination with LC-MS/MS-based proteomics arise as a powerful high-sensitive and non-invasive platform for the identification of biomarkers at extremely low concentrations in a complex mixture [ 35 ]. Unlike conventional tissue biopsy, liquid biopsy is a non-invasive approach, which allows repeated analysis to enable monitoring tumor progression, metastasis, and recurrence, as well as treatment response.…”
Section: Proteomic Profiling Technologies and Big Datamentioning
confidence: 99%
“…Among them, aldo-keto reductase family 1 member B10 (AKR1B10) and cathepsin A (CTSA) in combination with AFP showed the greatest area under the curve (AUC). Additionally, MS-based plasma proteomic atlas containing 53 and 25 molecular biomarkers for HCC and cholangiocarcinoma, respectively, has been constructed to differentiate tumor stage and to assess post-operative prognosis [ 35 ]. Six and two HCC biomarkers were abundant in phase II and phase III HCC, respectively, including alpha-2-HS-glycoprotein and apolipoprotein CIII (both ≥0.2%), Ig λ-chain VI region NEWM (≥1.0%), and serum amyloid P component (≥0.3%), which positively correlated with the best OS and RFS.…”
Section: Screening For Novel Hcc Proteomic Biomarker Candidatesmentioning
confidence: 99%
“…Enroth et al found plasma protein biomarker signatures for ovarian cancer 22 , but performed no validation. He et al showed that for hepatocellular carcinoma and cholangiocarcinoma, biomarker candidates could be identified from plasma; validation of these candidates is still pending 23 . Zhou et at.…”
Section: Introductionmentioning
confidence: 99%